CONTRIBUTIONS OF THE SCIENTISTS FROM CLUJ TO THE COSMIC SPACE RESEARCH - RISTOIU, Dumitru (Studia Universitatis Babeș-Bolyai Ambientum, 2017)
It is now widely accepted that modern investigations for research of complex processes occurring in the atmospheres of the planets began on Oct. 4, 1957 with the orbiting of the Earth’s first artificial satellite. With the launch of the first rockets and satellites in space, there are “unexpected” discoveries world-wide in this domain. Thus, in 1958, van Allen radiation belts around the Earth (Henry Elliot, 1959) were discovered, which led to the launch of laborious scientific programs for the study of Earth’s Higher Atmosphere in all aspects (electrical, magnetic, chemical, etc.). Investigation of neutral and ionized constituents from upper atmosphere of the Earth represent an important parameter for solving some geophysical and astrophysical problems. For example, atmospheric pressure and temperature can not be accurately measured or determined without knowing very well the composition of the neutral constituents. The problem of locating the gas gravity separation level can only be solved only after a detailed investigation of the neutral atmosphere composition. Knowing the structure of the atmosphere is the basic requirement for investigation of other physical processes from the Earth atmosphere. The work is a history of the main investigating institutes from Cluj-Napoca who were involved in the initiation, development and construction of equipment for the major investigate the outer space and for conducting observations of trajectories of artificial satellites.